Effectiveness Analysis Group Counseling Peer Assessment Techniques To Strengthen Student Class XI Specialisation MIA 1 SMA 1 Jekulo Kudus Academic Year 2014/2015 - Su cipto; A. Kiswantoro (Empati-Jurnal Bimbingan dan Konseling, 2016)
The research objective was to analyze the effectiveness of group counseling, peer assessment techniques in establishing specialization class XI SMA MIA 1 SMA 1 Jekulo Kudus academic year 2015/2016. Specialisation learners is a process of making choices and decisions by learners in the areas of expertise that are based on understanding of the potential and opportunities that exist. Peer group counseling techniques peer assessment is an assessment based on the observation and understanding held to foster a sense of responsibility of students were assessed for behavior and to motivate students to make improvements, as well as helping the counselee (students) in the decision to eradicate the problem. This research is a class action through two cycles. The independent variables were peer assessment group counseling techniques, while the dependent variable is the steadiness of specialization students place the implementation of this research is student class X MIA 1in the SMA 1 Jekulo Kudus academic year 2014/2015. Subjects assigned 9 (nine) students who have unstable in determining the choice of interest are currently being practiced. The results showed assessment peer group counseling techniques to increase the stability of specialization class XI A-1 the SMA 1 ?é?áJekulo Kudus academic year 2014/2015 at the end of the first cycle in the category of "enough" improve to the category of "good" in the second cycle. Counseling group peer assessment techniques is one of the counseling model which is applied to help improve the stabilization of specialization students, but it has other impacts for personal development and adjustment of students better. Conclusions of research that is peer assessment group counseling techniques proven effective to improve the stability of specialization class XI A-1 SMA 1 Jekulo Kudus?é?á year 2014/2015. Recommendations for school counselors need to apply this model especially in high school where the students are currently studying individuals who search for identity and the need to input / assessment of more friends. Key word: ?é?áGroup Counseling peer assessment techniques; specializations